Molecular Characterization of Grass Carp GIPR and Effect of Nutrition States, Insulin, and Glucagon on Its Expression. (7th November 2022) - Yang, Guokun; Liang, Xiaomin; Jiang, Yanle; Li, Chengquan; Zhang, Yanmin; Zhang, Xindang; Chang, Xulu; Shen, Yawei; Meng, Xiaolin
Abstract : GIP plays an important regulatory role in glucose and lipid metabolism. As the specific receptor, GIPR is involved in this physiological process. To assess the roles of GIPR in teleost, the GIPR gene was cloned from grass carp. The ORF of cloned GIPR gene was 1560 bp, encoding 519 amino acids. The grass carp GIPR was the G-protein-coupled receptor which contains seven predicted transmembrane domains. In addition, two predicted glycosylation sites were contained in the grass carp GIPR. The grass carp GIPR expression is in multiple tissues and is highly expressed in the kidney, brain regions, and visceral fat tissue. In the OGTT experiment, the GIPR expression is markedly decreased in the kidney, visceral fat, and brain by treatment with glucose for 1 and 3 h. In the fast and refeeding experiment, the GIPR expression in the kidney and visceral fat tissue was significantly induced in the fast groups. In addition, the GIPR expression levels were markedly decreased in the refeeding groups. In the present study, the visceral fat accumulation of grass carp was induced by overfed. The GIPR expression was significantly decreased in the brain, kidney, and visceral fat tissue of overfed grass carp. In primary hepatocytes, the GIPR expression was promoted by treatment with oleic acid and insulin. The GIPR mRNA levels were significantly reduced by treatment with glucose and glucagon in the grass carp primary hepatocytes. To our knowledge, this is the first time the biological role of GIPR is unveiled in teleost.